Zinc oxide functionalized calcium carbonate composite material

By producing zinc oxide functionalized calcium carbonate composites, the problem of instability of aqueous preparations during storage and treatment is solved, the stability and optical performance of the product are improved, and the use of amine stabilizers is avoided.

CN119855876APending Publication Date: 2025-04-18OMYA INT AG
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380064419.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-09
Filing Date
2023-08-29
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

Existing aqueous formulations are prone to instability during storage and treatment, affecting their mechanical and optical properties. Commonly used amine stabilizers may cause the product to be highly alkaline, have poor odor and decrease in optical properties.

Method used

Production of zinc oxide functionalized calcium carbonate composites by a method including providing a calcium carbonate-containing material and a source of water-soluble or water-dispersible zinc ions, preparing an aqueous suspension and heating to at least 60°C, then drying and heat treatment in the range of 250-550°C to obtain zinc oxide functionalized calcium carbonate composites.

Benefits of technology

This composite material can improve the storage stability of aqueous formulations and solid products, avoid the use of amine stabilizers, and solve the problems of product stability and optical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005301002270000251
    Figure BDA0005301002270000251
  • Figure BDA0005301002270000252
    Figure BDA0005301002270000252
  • Figure BDA0005301002270000261
    Figure BDA0005301002270000261
Patent Text Reader

Abstract

The present invention relates to a process for preparing a zinc oxide-functionalized calcium carbonate composite, a zinc oxide-functionalized calcium carbonate composite obtainable by this process, an article comprising a zinc oxide-functionalized calcium carbonate composite and the use of a zinc oxide-functionalized calcium carbonate composite in an aqueous formulation or a solid article.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing a zinc oxide functionalized calcium carbonate composite material, a zinc oxide functionalized calcium carbonate composite material obtained by a method, a product comprising the zinc oxide functionalized calcium carbonate composite material, and use of the zinc oxide functionalized calcium carbonate composite material in an aqueous preparation or a solid product. Background Art

[0002] In practice, water-insoluble solids such as minerals, fillers or pigments, aqueous preparations and especially suspensions, emulsions, dispersions or slurries are widely used in the paper, paint, rubber and plastic industries as coatings, fillers, extenders and pigments for papermaking and water-based varnishes and paints. For example, suspensions or slurries of calcium carbonate, talc or kaolin are used in large quantities in the papermaking industry as fillers and / or components in the preparation of coated paper. In addition, such aqueous preparations are also used as additives in concrete and agricultural industries. Typical aqueous preparations of water-insoluble solids are characterized in that they contain water, water-insoluble solid compounds and optional other additives such as dispersants, in the form of suspensions, slurries or dispersions, wherein the water-insoluble solid content is 0.1-99.0% by weight of the total weight of the preparation. A typical aqueous preparation is a white mineral dispersion (WMD) with a solid content of 45.0-78.0% by weight. Water-soluble polymers and copolymers which can be used, for example, as dispersants and / or grinding aids in such formulations are described, for example, in US Pat. No. 5,278,248.

[0003] The above aqueous formulations often become unstable during storage and handling, which affects their mechanical and optical properties. Therefore, manufacturers of such formulations usually stabilize suspensions, dispersions or slurries by adding corresponding compounds and compositions.

[0004] For example, amine-based pH stabilization systems (suitable for maintaining the pH of aqueous formulations) are well known and widely used. However, the problem with such amines is that they can make aqueous formulations highly alkaline (i.e., pH values ​​exceeding 12), requiring specific work safety measures and specific labeling of the final product as corrosive. In addition, amines decompose over time, which leads to deterioration of optical properties (e.g., yellowing of the product) and the generation of unpleasant odors. Summary of the invention

[0005] Therefore, the object of the present invention is to provide a compound suitable for improving the storage stability of products such as aqueous preparations and solid products. Another object of the present invention is to provide a method for preparing such a compound. A further object of the present invention is to provide a storage-stable compound or composition without the use of amines. Another object of the present invention is to provide a method for stabilizing the product accordingly.

[0006] The aforementioned objects as well as other objects are solved by the subject matter defined herein in the independent claims.Preferred embodiments of the inventive method, zinc oxide functionalized calcium carbonate composite material, articles and uses are defined in the corresponding dependent claims.

[0007] According to one aspect of the present invention, a method for producing a zinc oxide functionalized calcium carbonate composite material is provided. The method for producing a zinc oxide functionalized calcium carbonate composite material comprises the following steps:

[0008] a) providing a calcium carbonate-containing material;

[0009] b) providing at least one water-soluble or water-dispersible zinc ion source;

[0010] c) preparing an aqueous suspension comprising the calcium carbonate-comprising material of step a) and the at least one water-soluble or water-dispersible zinc ion source of step b) under mixing, and heating the aqueous suspension to a temperature of at least 60° C.;

[0011] d) drying the aqueous suspension of step c) to obtain a dried mixture; and

[0012] e) heat treating the dried mixture obtained in step d) at a temperature in the range of 250-550° C. to obtain the zinc oxide functionalized calcium carbonate composite material.

[0013] According to one embodiment, the calcium carbonate-containing material is selected from the group consisting of natural ground calcium carbonate, synthetic precipitated calcium carbonate and mixtures thereof, preferably natural ground calcium carbonate.

[0014] According to another embodiment, the at least one water-soluble or water-dispersible zinc ion source is at least one zinc salt, preferably a zinc salt selected from zinc chloride, zinc sulfate, zinc nitrate, zinc citrate, zinc maleate, zinc acetate, zinc lactate and mixtures thereof, preferably, the zinc salt is zinc chloride.

[0015] According to yet another embodiment, the calcium carbonate-comprising material of step a) is provided in the form of an aqueous suspension, and / or the at least one water-soluble or water-dispersible zinc ion source of step b) is provided in the form of an aqueous suspension or an aqueous solution or a solid material.

[0016] According to one embodiment, the aqueous suspension of step c) is prepared by mixing the at least one water-soluble or water-dispersible zinc ion source of step b), preferably mixing the at least one water-soluble or water-dispersible zinc ion source of step b) as a solid material into the aqueous suspension of the calcium carbonate-comprising material of step a).

[0017] According to another embodiment, the at least one water-soluble or water-dispersible zinc ion source of step b) is present in an amount (measured as Zn ions) of 1-40 wt.-%, preferably 3-35 wt.-%, most preferably 5-30 wt.-%, based on the total weight of the calcium carbonate-comprising material.

[0018] According to yet another embodiment, the heating in step c) is carried out at a temperature of 60-100°C, preferably 60-90°C, most preferably 60-75°C.

[0019] According to one embodiment, the drying in step d) is carried out by mechanical dehydration, filtration and / or evaporation.

[0020] According to another embodiment, the dried mixture has a solids content of 80-99.9% by weight, preferably 85-99.8% by weight, most preferably 90-99.5% by weight, based on the total weight of the mixture obtained.

[0021] According to yet another embodiment, the heat treatment in step e) is carried out at a temperature of 250-500°C, most preferably 250-450°C.

[0022] According to one embodiment, the zinc oxide functionalized calcium carbonate composite material has a BET specific surface area of ​​1.0-70.0 m 2 / g, preferably 1.0-65.0m 2 / g, most preferably 1.0-60.0m 2 / g, measured according to ISO 9277 using nitrogen and the BET method.

[0023] According to another embodiment, the method comprises the further step f): mixing the zinc oxide functionalized calcium carbonate composite material and a dispersant.

[0024] According to another aspect of the present invention, there is provided a zinc oxide functionalized calcium carbonate composite material obtainable by the method defined herein.

[0025] According to a further aspect of the present invention, there is provided an article comprising the zinc oxide functionalized calcium carbonate composite material as defined herein, the article being an aqueous preparation, preferably a papermaking formulation, a paper coating formulation, a fiber formulation, a plastic formulation, an adhesive formulation, a metalworking fluid, a cooling fluid, a primercoat, a leveling compound, a pigment formulation, a titanium dioxide slurry, a concrete additive formulation, a binder formulation, a thickener formulation, a plaster, a coating, a render, a varnish and / or a paint formulation, or a solid article, preferably a coating, a paint film, a varnish or a coating, a paper coating, paper, paperboard, an adhesive, a sealant, a pigment, a fiber, a plaster, a plaster-spray, a gypsum plasterboard, a binder, a thickener, a gypsum and / or concrete.

[0026] According to one embodiment, the preparation is an aqueous formulation comprising a dispersant.

[0027] According to a further aspect of the present invention, there is provided the use of a zinc oxide functionalized calcium carbonate composite material as defined herein in an aqueous formulation, preferably a papermaking formulation, a paper coating formulation, a fiber formulation, a plastic formulation, an adhesive formulation, a metalworking fluid, a cooling fluid, a primer, a leveling compound, a pigment formulation, a titanium dioxide slurry, a concrete additive formulation, a binder formulation, a thickener formulation, a plaster, a render, a coating, a varnish and / or a paint formulation, or a solid article, preferably a coating, a paint film, a varnish or a coating, a paper coating, paper, paperboard, an adhesive, a sealant, a pigment, a fiber, a plaster, a plaster spray, a gypsum plasterboard, a binder, a thickener and / or concrete.

[0028] According to one embodiment, the zinc oxide-functionalized calcium carbonate composite material improves the storage stability of an aqueous formulation or a solid product.

[0029] The present inventors have surprisingly found that the above method provides a composite suitable for improving the storage stability of products such as aqueous formulations and solid products.

[0030] More particularly, the present inventors have found that if a zinc oxide functionalized calcium carbonate composite is used, storage stability of products such as aqueous formulations and solid products can be achieved.

[0031] It should be noted that a variety of attempts have been made to prepare composite materials comprising zinc oxide and calcium carbonate. For example, "Characterization and applications of a new composite material obtained by green synthesis, through deposition of zinc oxide onto calcium carbonate precipitated in green seaweeds extract" (CERAMICS INTERNATIONAL, ELSEVIER, AMSTERDAM, NL, vol. 44, no. 5, December 13, 2017, pp. 4931-4936) by Anca Dumbrava et al. relates to a composite material obtained by depositing zinc oxide on calcium carbonate precipitated in green algae extract. However, the method of Anca Dumbrava et al. not only lacks the steps c), d) and e) required by the method of the present invention, but also requires the presence of additives such as polysaccharides that are not used in the present invention. Therefore, the composite material obtained by Anca Dumbrava et al. is not the result of the heat treatment required for the zinc oxide functionalized calcium carbonate composite material of the present invention, but is only a physical mixture of the components used. There are significant differences between the composite material obtained by this physical mixture and the composite material obtained by heat treatment. In particular, the composite material obtained from the physical mixture comprises rod-shaped zinc oxide particles deposited only on a portion of the calcium carbonate surface (see Anca Dumbrava et al. Figure 2 And the present invention Figure 2 ). In contrast, the composite material obtained by the heat treatment claimed in the present invention provides a calcium carbonate surface fully functionalized / treated with zinc species (see Figure 1 ). It is further known that Anca Dumbrava et al. disclose that zinc oxide powder has been added to the filtrate of specially treated seaweed, thereby eliminating the need to convert the zinc compound into zinc oxide by heat treatment. In contrast, the present invention requires at least one water-soluble or water-dispersible zinc ion source, which is thermally converted into zinc oxide on the surface of calcium carbonate to obtain the zinc oxide functionalized calcium carbonate composite material of the present invention.

[0032] Where an indefinite or definite article is used when referring to a singular noun eg "a", "an" or "the", this includes a plural of that noun unless otherwise specifically stated anywhere.

[0033] When the term "comprising" is used in the present description and claims, it does not exclude other elements. For the purpose of the present invention, the term "consisting of" is considered to be a preferred embodiment of the term "comprising". If a group is defined below to include at least a certain number of embodiments, this is also understood to disclose a group that preferably consists of these embodiments only.

[0034] Terms such as "obtainable" or "definable" and "obtained" or "defined" are used interchangeably. This means, for example, that unless the context clearly indicates otherwise, the term "obtained" is not meant to indicate, for example, that an embodiment must be obtained by, for example, the sequence of steps following the term "obtained", although the term "obtained" or "defined" always includes such a restrictive understanding as a preferred embodiment.

[0035] Wherever the terms "including" or "having" are used, these terms are considered equivalent to "comprising" as defined above.

[0036] The preferred embodiments of the method of the present invention will be described in more detail below. It should be understood that these embodiments and details are equally applicable to the zinc oxide functionalized calcium carbonate composite material, products and uses of the present invention within the applicable scope. It should be understood by those skilled in the art that many embodiments described herein can be combined or applied together.

[0037] Method for producing zinc oxide functionalized calcium carbonate composite material

[0038] According to step a) of the method, a calcium carbonate-containing material is provided.

[0039] In one embodiment of the present invention, the calcium carbonate-containing material is selected from natural ground calcium carbonate, synthetic precipitated calcium carbonate and mixtures thereof. Thus, in one embodiment, the calcium carbonate-containing material is natural ground calcium carbonate or synthetic precipitated calcium carbonate. In another embodiment, the calcium carbonate-containing material is a mixture of natural ground calcium carbonate and synthetic precipitated calcium carbonate.

[0040] Preferably, the calcium carbonate-containing material is natural ground calcium carbonate.

[0041] "Natural ground calcium carbonate" (GCC) within the meaning of the present invention refers to a calcium carbonate which has been obtained from a natural source such as limestone, marble or chalk and has been subjected to treatments such as dry and / or wet grinding, screening and / or classification (e.g. with the aid of cyclones or classifiers).

[0042] "Synthetic precipitated calcium carbonate" (PCC) within the meaning of the present invention refers to a synthetic material, usually obtained by precipitation following reaction of carbon dioxide with lime in an aqueous environment, or by precipitation of a source of calcium and carbonate ions in water.

[0043] Unlike other uses of calcium carbonate-containing materials, the material (preferably natural ground calcium carbonate and / or synthetic precipitated calcium carbonate) is not surface treated and / or does not contain a dispersant. Preferably, the calcium carbonate-containing material (preferably natural ground calcium carbonate and / or synthetic precipitated calcium carbonate) is not surface treated and does not contain a dispersant.

[0044] It should be noted that the synthetic precipitated calcium carbonate (PCC) of the present invention is preferably different from the calcium carbonate precipitated in green seaweeds extract.

[0045] Additionally or alternatively, the calcium carbonate-containing material provided in step a) is different from the surface-reacted calcium carbonate as described in EP3275947A1. Therefore, the calcium carbonate-containing material provided in step a) is preferably not a surface-reacted calcium carbonate. In particular, the calcium carbonate-containing material provided in step a) is neither prepared by reacting the calcium carbonate in an aqueous medium with at least one HO + The zinc oxide functionalized calcium carbonate composite material of the present invention is preferably free of phosphate. Therefore, the calcium carbonate-containing material provided in step a) is preferably not surface-reacted calcium carbonate, and the zinc oxide functionalized calcium carbonate composite material of the present invention is preferably free of surface-reacted calcium carbonate.

[0046] In very general terms, the calcium carbonate-containing material may have a particle size distribution as is conventionally employed for materials of the type of product to be produced. Generally, it is preferred that the calcium carbonate-containing material has a weight median particle size d 50 The value is 0.1-5 μm, preferably 0.2-2 μm, most preferably 0.35-1 μm, for example 0.7 μm, using a Sedigraph from Micromeritics Instrument Corporation TM 5120 measurements.

[0047] In one embodiment, the calcium carbonate-comprising material is provided in the form of an aqueous suspension.

[0048] Therefore, the aqueous preparation is preferably an aqueous suspension (or slurry).

[0049] It is to be understood that the solid content of the aqueous suspension may be up to 85.0% by weight. For example, the solid content of the aqueous suspension is 05.0-82.0% by weight, preferably 0.5.0-80.0% by weight, most preferably 0.5-60.0% by weight, based on the total weight of the aqueous suspension.

[0050] The total solids content within the meaning of the present invention corresponds to the residual weight of the aqueous preparation measured in a sample of at least 3 to 5 g after drying at 105° C. for 3 hours.

[0051] Typically, the aqueous suspension has a viscosity of preferably 50-2 000 mPa·s, preferably 80-800 mPa·s, measured using a Brookfield DV-II viscometer equipped with a LV-3 spindle at a rotation speed of 100 rpm.

[0052] The aqueous suspension according to the invention may be produced by methods known in the art, for example by dispersing, suspending or slurrying the calcium carbonate-comprising material in water.

[0053] According to step b) of the process, at least one water-soluble or water-dispersible source of zinc ions is provided.

[0054] The term "at least one" water-soluble or water-dispersible zinc ion source within the meaning of the present invention means that the source comprises, preferably consists of, one or more water-soluble or water-dispersible zinc ion sources.

[0055] In one embodiment of the invention, the water-soluble or water-dispersible zinc ion source comprises one water-soluble or water-dispersible zinc ion source, preferably consisting of one water-soluble or water-dispersible zinc ion source. Alternatively, the water-soluble or water-dispersible zinc ion source comprises two or more water-soluble or water-dispersible zinc ion sources, preferably consisting of two or more water-soluble or water-dispersible zinc ion sources. For example, the water-soluble or water-dispersible zinc ion source comprises two or three water-soluble or water-dispersible zinc ion sources, preferably consisting of two or three water-soluble or water-dispersible zinc ion sources. Preferably, the water-soluble or water-dispersible zinc ion source comprises one water-soluble or water-dispersible zinc ion source, preferably consisting of one water-soluble or water-dispersible zinc ion source.

[0056] It is to be understood that the at least one water-soluble or water-dispersible zinc ion source of step b) may be any material comprising zinc ions as ions or consisting of zinc ions as ions.

[0057] It is to be understood that the at least one zinc ion source is water soluble or water dispersible.

[0058] Therefore, the term "water-soluble" or "soluble in water" in the meaning of the present invention refers to a system in which the zinc ion source forms a solution with water, i.e. the particles of the at least one zinc ion source are dissolved in the solvent. Alternatively, the term "water-dispersible" or "dispersible in water" in the meaning of the present invention refers to a system in which only a portion of the zinc ion source forms a solution with water, i.e. only a portion of the particles of the at least one zinc ion source are dissolved in the solvent.

[0059] The term "source" of zinc ions within the meaning of the present invention refers to a compound comprising zinc ions.

[0060] The at least one water-soluble or water-dispersible zinc ion source is preferably at least one zinc salt. Preferably, the zinc salt is selected from the group comprising the following substances, preferably from the group consisting of the following substances: zinc chloride, zinc sulfate, zinc nitrate, zinc citrate, zinc maleate, zinc acetate, zinc lactate and mixtures thereof.

[0061] For example, the at least one zinc salt is zinc chloride.

[0062] In one embodiment, the at least one water-soluble or water-dispersible zinc ion source is provided in the form of an aqueous suspension or aqueous solution, depending on the solubility of the at least one water-soluble or water-dispersible zinc ion source in water. Alternatively, the at least one water-soluble or water-dispersible zinc ion source is provided in the form of a solid material.

[0063] It should be understood that the content of the at least one water-soluble or water-dispersible zinc ion source in the aqueous suspension or aqueous solution can be up to 85.0% by weight. For example, the content of the at least one water-soluble or water-dispersible zinc ion source in the aqueous suspension or aqueous solution is 05.0-82.0% by weight, preferably 0.5.0-80.0% by weight, and most preferably 0.5-60.0% by weight, based on the total weight of the aqueous suspension or aqueous solution.

[0064] The aqueous suspension or aqueous solution according to the invention can be produced by methods known in the art, for example by dispersing, suspending or slurrying or dissolving the at least one water-soluble or water-dispersible zinc ion source in water.

[0065] According to step c) of the process, an aqueous suspension comprising the calcium carbonate-comprising material of step a) and the at least one water-soluble or water-dispersible zinc ion source of step b) is prepared under mixing and the aqueous suspension is heated to a temperature of at least 60°C.

[0066] Preferably, the aqueous suspension of step c) is prepared by mixing the at least one water-soluble or water-dispersible zinc ion source of step b) into the aqueous suspension of the calcium carbonate-comprising material of step a).

[0067] The at least one water-soluble or water-dispersible zinc ion source of step b) is added to the aqueous suspension of the calcium carbonate-containing material of step a) in the form of an aqueous suspension, an aqueous solution or a solid material.

[0068] Preferably, the at least one water-soluble or water-dispersible zinc ion source of step b) is added to the aqueous suspension of the calcium carbonate-comprising material of step a) in the form of a solid material.

[0069] In the aqueous suspension prepared in step c), the at least one water-soluble or water-dispersible zinc ion source of step b) is present in an amount (measured as Zn ions) of 1 to 40% by weight, based on the total weight of the calcium carbonate-containing material.

[0070] Preferably, the at least one water-soluble or water-dispersible zinc ion source of step b) is present in the aqueous suspension in an amount (measured as Zn ions) of 3-35 wt.-%, most preferably 5-30 wt.-%, based on the total weight of the calcium carbonate-containing material.

[0071] Preferably, the aqueous suspension comprising the calcium carbonate-containing material of step a) and the at least one water-soluble or water-dispersible zinc ion source of step b) does not contain additives such as polysaccharides, especially polysaccharide sodium salts (e.g. from green algae). That is, the zinc oxide functionalized calcium carbonate composite material obtained by the method preferably does not contain additives such as polysaccharides, especially polysaccharide sodium salts (e.g. from green algae).

[0072] It is to be understood that the aqueous suspension prepared in step c) is heated to a temperature of at least 60° C. to enhance the interaction of the at least one water-soluble or water-dispersible zinc ion source with the calcium carbonate-containing material. This enhanced interaction is advantageous for improving the distribution and precipitation of the at least one water-soluble or water-dispersible zinc ion source on the surface of the calcium carbonate-containing material in the drying step d).

[0073] Preferably, the heating in step c) is carried out at a temperature of 60-100° C., preferably 60-90° C., most preferably 60-85° C., for example 60-75° C. In one embodiment, the heating in step c) is carried out at a temperature of 65-100° C., preferably 65-90° C., most preferably 65-85° C. In another embodiment, the heating in step c) is carried out at a temperature of 70-100° C., preferably 70-90° C., most preferably 70-85° C.

[0074] According to step d) of the process, the aqueous suspension of step c) is dried to obtain a dried mixture.

[0075] Advantageously for the precipitation of the at least one water-soluble or water-dispersible zinc ion source on the surface of the calcium carbonate-comprising material, the aqueous suspension obtained in step c) is dried before being subjected to a heat treatment in step e).

[0076] The drying of the aqueous suspension in step d) can be carried out by any known means of reducing the water content of an aqueous suspension, thus, the drying in step d) is carried out by mechanical dehydration, filtration and / or evaporation. For example, the drying step d) is carried out by mechanical dehydration.

[0077] The drying is preferably carried out so that the dried mixture has a solid content of 80-99.9% by weight, more preferably 85-99.8% by weight, most preferably 90-99.5% by weight, based on the total weight of the mixture obtained. That is, the dried material obtained in step d) has a moisture content of 0.1-20% by weight, more preferably 0.2-15% by weight, most preferably 0.5-10% by weight, based on the total weight of the mixture obtained.

[0078] For example, the drying in step d) is carried out at a temperature of 110-200° C., preferably 110-190° C., most preferably 110-180° C., for example 110-170° C. In one embodiment, the drying in step d) is carried out at a temperature of 120-200° C., preferably 120-190° C., most preferably 120-180° C., for example 120-170° C. In another embodiment, the drying in step d) is carried out at a temperature of 130-200° C., preferably 130-190° C., most preferably 130-180° C., for example 130-170° C.

[0079] In one embodiment, the drying in step d) is carried out by mechanical dehydration, filtration and / or evaporation followed by a drying step carried out at a temperature of 110-200° C., preferably 110-190° C., most preferably 110-180° C., for example 110-170° C. For example, the drying in step d) is carried out by mechanical dehydration, filtration and / or evaporation followed by a drying step carried out at a temperature of 120-200° C., preferably 120-190° C., most preferably 120-180° C., for example 120-170° C. For example, the drying in step d) is carried out by mechanical dehydration, filtration and / or evaporation followed by a drying step carried out at a temperature of 130-200° C., preferably 130-190° C., most preferably 130-180° C., for example 130-170° C.

[0080] Particularly good results are obtained if the drying in step d) is carried out by mechanical dehydration followed by drying at a temperature of 110-200° C., preferably 110-190° C., most preferably 110-180° C., for example 110-170° C. For example, the drying in step d) is carried out by mechanical dehydration followed by a drying step at a temperature of 120-200° C., preferably 120-190° C., most preferably 120-180° C., for example 120-170° C. For example, the drying in step d) is carried out by mechanical dehydration followed by a drying step at a temperature of 130-200° C., preferably 130-190° C., most preferably 130-180° C., for example 130-170° C.

[0081] The present invention particularly requires that the dried mixture obtained in step d) is subjected to a heat treatment at a temperature ranging from 250 to 550° C. to obtain the zinc oxide functionalized calcium carbonate composite material. The heat treatment is decisive to convert the at least one water-soluble or water-dispersible zinc ion source into zinc oxide and thus prepare the zinc oxide functionalized calcium carbonate composite material.

[0082] According to step e) of the present invention, the method thus comprises step e) of heat treating the dried mixture obtained in step d) at a temperature ranging from 250 to 550° C., so as to obtain the zinc oxide functionalized calcium carbonate composite material.

[0083] It is to be understood that temperatures above 250° C. are necessary to convert the at least one water-soluble or water-dispersible zinc ion source into zinc oxide. However, temperatures above 550° C. are to be avoided in order to prevent (complete) conversion of the calcium carbonate-comprising material into calcium oxide.

[0084] In a preferred embodiment, the heat treatment in step e) is carried out at a temperature of 250-500° C., most preferably 250-450° C. For example, the heat treatment in step e) is carried out at a temperature of 275-500° C., most preferably 275-450° C. Alternatively, the heat treatment in step e) is carried out at a temperature of 300-500° C., most preferably 300-450° C. In a preferred embodiment, the heat treatment in step e) is carried out at a temperature of 310-400° C., most preferably 310-380° C.

[0085] The zinc oxide functionalized calcium carbonate composite material has a BET specific surface area of ​​1.0-70.0 m2 measured using nitrogen and the BET method according to ISO 9277. 2 For example, the zinc oxide functionalized calcium carbonate composite material has a BET specific surface area of ​​1.0-65.0 m2 measured using nitrogen and BET method according to ISO 9277. 2 / g, most preferably 1.0-60.0m 2 / g.

[0086] In one embodiment, the zinc oxide functionalized calcium carbonate composite material comprises natural ground calcium carbonate and has a BET specific surface area of ​​1.0-60.0 m2 measured using nitrogen and the BET method according to ISO 9277. 2 / g, preferably 1.0-40.0m 2 / g, most preferably 1.0-30.0m 2 In another embodiment, the zinc oxide functionalized calcium carbonate composite material comprises synthetic precipitated calcium carbonate and has a BET specific surface area of ​​10.0-70.0 m2 measured using nitrogen and the BET method according to ISO 9277. 2 / g, preferably 20.0-65.0m 2 / g, most preferably 30.0-60.0m 2 / g.

[0087] In one embodiment, the zinc oxide functionalized calcium carbonate composite material has a weight median particle size d 50 ≤20 μm, preferably ≤6 μm, more preferably ≤3 μm, and most preferably ≤2 μm. For example, the zinc oxide functionalized calcium carbonate composite material of the present invention has a weight median particle size d 50 It is 0.1-20 μm, preferably 0.2-6 μm, more preferably 0.4-3 μm, and most preferably 0.5-2 μm.

[0088] Additionally or alternatively, the zinc oxide functionalized calcium carbonate composite material has a top cut particle size d 98 ≤200 μm, preferably ≤20 μm, more preferably ≤10 μm, and most preferably ≤8 μm. For example, the zinc oxide functionalized calcium carbonate composite material of the present invention has a top cut particle size d 98 It is 0.5-200 μm, preferably 1-20 μm, more preferably 1.5-10 μm, and most preferably 2-8 μm.

[0089] In one embodiment, the zinc oxide functionalized calcium carbonate composite material preferably has:

[0090] -Weight median particle size d 50 ≤20 μm, preferably ≤6 μm, more preferably ≤3 μm, most preferably ≤2 μm; and

[0091] - Top cut particle size d 98 It is ≤200 μm, preferably ≤20 μm, more preferably ≤10 μm, and most preferably ≤8 μm.

[0092] Therefore, the zinc oxide functionalized calcium carbonate composite material preferably has:

[0093] -BET surface area measured using nitrogen and BET method according to ISO 9277 is 1.0-70.0 m 2 / g, preferably 1.0-65.0.0m 2 / g, most preferably 1.0-60.0m 2 / g, and

[0094] -Weight median particle size d 50 ≤20 μm, preferably ≤6 μm, more preferably ≤3 μm, most preferably ≤2 μm; and

[0095] - Top cut particle size d 98 It is ≤200 μm, preferably ≤20 μm, more preferably ≤10 μm, and most preferably ≤8 μm.

[0096] In one embodiment, the zinc oxide functionalized calcium carbonate composite material may be provided with a dispersant well known to those skilled in the art. Such a dispersant is added to keep the zinc oxide functionalized calcium carbonate composite material dispersed in the aqueous formulation and thus ensure that the viscosity of the formulation remains substantially the same over time.

[0097] Suitable dispersants according to the present invention are preferably, but not limited to, homopolymers or copolymers made from monomers or comonomers selected from the group consisting of acrylic acid, methacrylic acid, itaconic acid, crotonic acid, fumaric acid, maleic anhydride, isocrotonic acid, aconitic acid (cis or trans), mesaconic acid, sinapic acid, undecylenic acid, angelic acid, canellic acid, hydroxyacrylic acid, acrolein, acrylamide, acrylonitrile, dimethylaminoethyl methacrylate, vinylpyrrolidone, styrene, esters of acrylic acid and methacrylic acid and mixtures thereof, wherein salts of poly(acrylic acid) and / or poly(methacrylic acid) are preferred as dispersants.

[0098] Therefore, the method of the present invention may comprise a further step f): mixing the zinc oxide functionalized calcium carbonate composite with a dispersant.

[0099] In this embodiment, the method for producing a zinc oxide functionalized calcium carbonate composite material comprises the following steps:

[0100] a) providing a calcium carbonate-containing material,

[0101] b) providing at least one water-soluble or water-dispersible zinc ion source,

[0102] c) preparing an aqueous suspension comprising the calcium carbonate-comprising material of step a) and the at least one water-soluble or water-dispersible zinc ion source of step b) under mixing, and heating the aqueous suspension to a temperature of at least 60° C.,

[0103] d) drying the aqueous suspension of step c) to obtain a dried mixture,

[0104] e) heat treating the dried mixture obtained in step d) at a temperature in the range of 250-550° C. to obtain the zinc oxide functionalized calcium carbonate composite material, and.

[0105] f) mixing the zinc oxide functionalized calcium carbonate composite material with a dispersant.

[0106] Step f) of mixing the zinc oxide functionalized calcium carbonate composite with a dispersant may be performed by any method known in the art.

[0107] For example, the zinc oxide-functionalized calcium carbonate composite is dispersed in water with the addition of a dispersant.

[0108] Composite materials, products and uses

[0109] Another aspect of the present invention relates to a zinc oxide functionalized calcium carbonate composite material obtainable by a process as defined herein.

[0110] The zinc oxide functionalized calcium carbonate composite material of the present invention has a BET specific surface area of ​​1.0-70.0 m2 measured by nitrogen and BET method according to ISO 9277. 2 For example, the zinc oxide functionalized calcium carbonate composite material has a BET specific surface area of ​​1.0-65.0 m2 measured by nitrogen and BET method according to ISO9277. 2 / g, most preferably 1.0-60.0m 2 / g.

[0111] In one embodiment, the zinc oxide functionalized calcium carbonate composite material comprises natural ground calcium carbonate and has a BET specific surface area of ​​1.0-50.0 m2 measured using nitrogen and the BET method according to ISO 9277. 2 / g, preferably 1.0-40.0m 2 / g, most preferably 1.0-30.0m 2 In another embodiment, the zinc oxide functionalized calcium carbonate composite material comprises synthetic precipitated calcium carbonate and has a BET specific surface area of ​​10.0-70.0 m2 measured using nitrogen and the BET method according to ISO 9277. 2 / g, preferably 20.0-65.0m 2 / g, most preferably 30.0-60.0m2 / g.

[0112] In one embodiment, the zinc oxide functionalized calcium carbonate composite material of the present invention has a weight median particle size d 50 ≤20 μm, preferably ≤6 μm, more preferably ≤3 μm, and most preferably ≤2 μm. For example, the zinc oxide functionalized calcium carbonate composite material of the present invention has a weight median particle size d 50 It is 0.1-20 μm, preferably 0.2-6 μm, more preferably 0.4-3 μm, and most preferably 0.5-2 μm.

[0113] Additionally or alternatively, the zinc oxide functionalized calcium carbonate composite material of the present invention has a top cut particle size d 98 ≤200 μm, preferably ≤20 μm, more preferably ≤10 μm, and most preferably ≤8 μm. For example, the zinc oxide functionalized calcium carbonate composite material of the present invention has a top cut particle size d 98 It is 0.5-200 μm, preferably 1-20 μm, more preferably 1.5-10 μm, and most preferably 2-8 μm.

[0114] In one embodiment, the zinc oxide functionalized calcium carbonate composite material of the present invention preferably has:

[0115] -Weight median particle size d 50 ≤20 μm, preferably ≤6 μm, more preferably ≤3 μm, most preferably ≤2 μm; and

[0116] - Top cut particle size d 98 It is ≤200 μm, preferably ≤20 μm, more preferably ≤10 μm, and most preferably ≤8 μm.

[0117] Therefore, the zinc oxide functionalized calcium carbonate composite material of the present invention preferably has:

[0118] -BET surface area measured using nitrogen and BET method according to ISO 9277 is 1.0-70.0 m 2 / g, preferably 1.0-65.0m 2 / g, most preferably 1.0-60.0m 2 / g, and

[0119] -Weight median particle size d 50 ≤20 μm, preferably ≤6 μm, more preferably ≤3 μm, most preferably ≤2 μm; and

[0120] - Top cut particle size d 98 It is ≤200 μm, preferably ≤20 μm, more preferably ≤10 μm, and most preferably ≤8 μm.

[0121] The zinc oxide functionalized calcium carbonate composite material can thus be obtained by a method comprising the following steps:

[0122] a) providing a calcium carbonate-containing material,

[0123] b) providing at least one water-soluble or water-dispersible zinc ion source,

[0124] c) preparing an aqueous suspension comprising the calcium carbonate-comprising material of step a) and the at least one water-soluble or water-dispersible zinc ion source of step b) under mixing, and heating the aqueous suspension to a temperature of at least 60° C.,

[0125] d) drying the aqueous suspension of step c) to obtain a dried mixture, and

[0126] e) heat treating the dried mixture obtained in step d) at a temperature in the range of 250-550° C. to obtain the zinc oxide functionalized calcium carbonate composite material.

[0127] In one embodiment, the zinc oxide functionalized calcium carbonate composite is provided together with a dispersant.

[0128] Thus, the zinc oxide functionalized calcium carbonate composite material can be obtained by a method comprising the following steps:

[0129] a) providing a calcium carbonate-containing material,

[0130] b) providing at least one water-soluble or water-dispersible zinc ion source,

[0131] c) preparing an aqueous suspension comprising the calcium carbonate-comprising material of step a) and the at least one water-soluble or water-dispersible zinc ion source of step b) under mixing, and heating the aqueous suspension to a temperature of at least 60° C.,

[0132] d) drying the aqueous suspension of step c) to obtain a dried mixture,

[0133] e) heat treating the dried mixture obtained in step d) at a temperature in the range of 250-550° C. to obtain the zinc oxide functionalized calcium carbonate composite material, and.

[0134] f) mixing the zinc oxide functionalized calcium carbonate composite material with a dispersant.

[0135] Regarding the method for producing the zinc oxide functionalized calcium carbonate composite material and its preferred embodiment, reference may be made to the description provided above in discussing the technical details of the method of the present invention.

[0136] The zinc oxide functionalized calcium carbonate composite material of the present invention improves the storage stability of an aqueous preparation or a solid product. Therefore, the aqueous preparation or the solid product can be any type of product that needs to be stabilized in storage.

[0137] More specifically, the product (such as an aqueous preparation or a solid product) comprises the zinc oxide-functionalized calcium carbonate composite material.

[0138] It should be understood that the zinc oxide functionalized calcium carbonate composite material is present in the article in an amount of at least 10 ppm, such as 10-27 000 ppm, preferably at least 25 ppm, such as 25-25 000 ppm, more preferably at least 50 ppm, such as 50-20000 ppm, even more preferably at least 60 ppm, such as 60-15 000 ppm, even more preferably at least 75 ppm, such as 75-10000 ppm, most preferably 75-5 000 ppm, calculated relative to the total weight of the article.

[0139] It is to be understood that the term "ppm" is calculated relative to the weight of the preparation (ie, aqueous preparation or solid preparation), unless otherwise indicated.

[0140] In one embodiment, the article may be an aqueous formulation, which is preferably a papermaking formulation, a paper coating formulation, a fiber formulation, a plastic formulation, an adhesive formulation, a metalworking fluid, a cooling fluid, a primer, a leveling compound, a pigment formulation, a titanium dioxide slurry, a concrete additive formulation, a binder formulation, a thickener formulation, a plaster, a coating, a render, a varnish and / or a paint formulation.

[0141] The aqueous preparation preferably comprises at least one inorganic particulate material.

[0142] The term "at least one" inorganic particulate material within the meaning of the present invention means that the inorganic particulate material comprises, preferably consists of, one or more inorganic particulate materials.

[0143] In one embodiment of the present invention, the at least one inorganic particulate material comprises one inorganic particulate material, preferably consisting of one inorganic particulate material. Alternatively, the at least one inorganic particulate material comprises two or more inorganic particulate materials, preferably consisting of two or more inorganic particulate materials. For example, the at least one inorganic particulate material comprises two or three inorganic particulate materials, preferably consisting of two or three inorganic particulate materials. Preferably, the at least one inorganic particulate material comprises one inorganic particulate material, preferably consisting of one inorganic particulate material.

[0144] For example, the at least one inorganic particulate material is selected from natural ground calcium carbonate, natural and / or synthetic precipitated calcium carbonate, dolomite, calcium sulfate, kaolin, clay, barite, talc, quartz, mica, gypsum, aluminum hydroxide, aluminum silicate, titanium dioxide, magnesite, hydromagnesite, hydroxyapatite, perlite, sepiolite, brucite and mixtures thereof.

[0145] In one embodiment of the present invention, the at least one inorganic particulate material comprises natural ground calcium carbonate and / or synthetic precipitated calcium carbonate. Preferably, the at least one inorganic particulate material comprises natural ground calcium carbonate or synthetic precipitated calcium carbonate.

[0146] It should be noted that hydromagnesite and brucite are added as the first buffer component of the buffer composition or the at least one inorganic particulate material of the aqueous formulation. That is, if the aqueous formulation contains hydromagnesite and / or brucite as the at least one inorganic particulate material, hydromagnesite and / or brucite are not included as the first buffer component in the buffer composition.

[0147] The natural ground calcium carbonate and / or the synthetic precipitated calcium carbonate and / or the surface-reacted calcium carbonate may additionally be subjected to a surface treatment known to the person skilled in the art.

[0148] If the aqueous formulation comprises at least one inorganic particulate material, the at least one inorganic particulate material may have a particle size distribution as is conventionally employed for materials involved in the type of product to be produced. Typically, 90% of the particles will have an esd (equivalent spherical diameter, measured by the well-known sedimentation method using a Micromeritics Sedigraph 5120 series) of less than 5 μm. Coarse inorganic particulate materials may have particles with an equivalent spherical diameter typically (i.e. at least 90% by weight) in the range of 1-5 μm. Fine inorganic particulate materials may have particles with an equivalent spherical diameter typically less than 2 μm, for example 50.0-99.0% by weight less than 2 μm, preferably 60.0-90.0% by weight less than 2 μm. Preferably, the at least one inorganic particulate material in the aqueous formulation has a weight median particle size d 50 The value is 0.1-5 μm, preferably 0.2-2 μm, most preferably 0.35-1 μm, for example 0.7 μm, measured using a Sedigraph™ 5120 from Micromeritics Instrument Corporation.

[0149] In order to keep the inorganic particulate material dispersed in the aqueous formulation and thus ensure that the viscosity of the formulation remains substantially the same over time, an additive such as a dispersant may be used. For example, the dispersant is preferably a homopolymer or copolymer made from monomers and / or comonomers selected from the group consisting of acrylic acid, methacrylic acid, itaconic acid, crotonic acid, fumaric acid, maleic anhydride, isocrotonic acid, aconitic acid (cis or trans), mesaconic acid, sinapic acid, undecylenic acid, angelic acid, canneric acid, hydroxyacrylic acid, acrolein, acrylamide, acrylonitrile, dimethylaminoethyl methacrylate, vinylpyrrolidone, styrene, esters of acrylic acid and methacrylic acid and mixtures thereof, wherein salts of poly(acrylic acid) and / or poly(methacrylic acid) are preferred as dispersants. Preferably, the dispersant is a dispersant based on acrylates or salts.

[0150] Additionally or alternatively, the aqueous formulation comprises at least one organic particulate material. For example, the at least one organic particulate material is selected from carbohydrates such as starch, sugar, cellulose, modified cellulose and cellulose-based pulp, glycerol, hydrocarbons, water-soluble polymers such as polyacrylates, and mixtures thereof.

[0151] It should be understood that the solid content of the aqueous formulation can be up to 85.0% by weight. For example, the solid content of the aqueous formulation is 05.0-82.0% by weight, preferably 0.5.0-80.0% by weight, most preferably 0.5-60.0% by weight, based on the total weight of the aqueous formulation.

[0152] The total solids content in the meaning of the present application corresponds to the residual weight of the aqueous preparation measured in a sample of at least 3-5 g after drying at 105° C. for 3 hours.

[0153] It should be noted that the aqueous preparation may contain a buffer component selected from an amine-based buffer component, a monoalcohol-based buffer component, a primary alkanolamine-based buffer component, a hydroxide-based buffer component, and a mixture thereof. For example, the aqueous preparation may contain a buffer component selected from the following items: ammonia, methylamine, dimethylamine, trimethylamine, diethylamine, propylamine, butylamine, hexylamine, amino-2-methylpropanol (AMP), monoethanolamine (MEA), monoisopropanolamine (MIPA), triethylenetetramine (TETA), calcium hydroxide, and a mixture thereof.

[0154] The pH of the aqueous preparation may vary within a wide range and is preferably within the pH range common to such aqueous preparations. It is therefore understood that the aqueous preparation preferably has a pH value of 2-12. For example, the aqueous preparation of step a) has a pH value of 6-11.5, more preferably 7-10.5.

[0155] Typically, the aqueous formulation has a viscosity of preferably 50-2000 mPa·s, preferably 80-800 mPa·s, measured using a Brookfield DV-II viscometer equipped with a LV-3 spindle at a rotation speed of 100 rpm.

[0156] The aqueous preparation according to the present invention can be produced by methods known in the art, for example by dispersing, suspending or slurrying a water-insoluble solid (preferably an inorganic particulate material) in water, adding a dispersant if necessary and, if necessary, other additives.

[0157] The aqueous formulation preferably has a pH of equal to or less than 12, preferably 4-12, more preferably 6-11.5, most preferably 8.5-10.5. Therefore, it is understood that the preparation as an aqueous formulation has a pH of equal to or less than 12, preferably 4-12, more preferably 6-11.5, most preferably 8.5-10.5.

[0158] The aqueous formulation is preferably prepared by a method comprising the following steps:

[0159] a) providing an aqueous formulation, preferably a papermaking formulation, a paper coating formulation, a fiber formulation, a plastic formulation, an adhesive formulation, a metalworking fluid, a cooling fluid, a primer, a leveling compound, a pigment formulation, a titanium dioxide slurry, a concrete additive formulation, a binder formulation, a thickener formulation, a plaster, a coating, a render, a varnish and / or a paint formulation;

[0160] b) providing a zinc oxide functionalized calcium carbonate composite material as defined herein; and

[0161] c) contacting and mixing the aqueous preparation of step a) with the zinc oxide-functionalized calcium carbonate composite material of step b) one or more times to obtain the aqueous preparation.

[0162] Regarding the definition of the zinc oxide functionalized calcium carbonate composite material and its preferred embodiments, reference may be made to the description provided above when discussing the technical details of the zinc oxide functionalized calcium carbonate composite material of the present invention.

[0163] According to step c) of the method of the present invention, the aqueous preparation of step a) is contacted and mixed with the zinc oxide-functionalized calcium carbonate composite material of step b).

[0164] Generally, the aqueous preparation of step a) and the zinc oxide-functionalized calcium carbonate composite of step b) can be contacted by any conventional means known to those skilled in the art.

[0165] It is to be understood that step c) is preferably performed by adding the zinc oxide functionalized calcium carbonate composite material of step b) to the aqueous formulation of step a).

[0166] Preferably, step c) is carried out by adding the zinc oxide functionalized calcium carbonate composite material to the aqueous formulation under mixing. Thorough mixing can be achieved by shaking the aqueous formulation or by stirring, which can provide more thorough mixing. In one embodiment of the present invention, step c) is carried out under stirring to ensure thorough mixing of the aqueous formulation and the zinc oxide functionalized calcium carbonate composite material. This stirring can be carried out continuously or discontinuously.

[0167] In one embodiment, step c) is carried out by adding the zinc oxide functionalized calcium carbonate composite material to the aqueous formulation in an amount such that the total amount of zinc oxide functionalized calcium carbonate composite material present in the aqueous formulation is at least 10 ppm, for example from 25 to 27000 ppm, preferably at least 25 ppm, for example 25-25000 ppm, more preferably at least 50 ppm, for example 50-20000 ppm, still more preferably at least 60 ppm, for example 60-15000 ppm, even more preferably at least 75 ppm, for example 75-10000 ppm, most preferably 75-5000 ppm, calculated relative to the total weight of the aqueous formulation.

[0168] It is to be understood that step c) may be repeated one or more times.

[0169] The zinc oxide functionalized calcium carbonate composite material can be added to the aqueous formulation in one or more portions. If the zinc oxide functionalized calcium carbonate composite material is added in multiple portions, the zinc oxide functionalized calcium carbonate composite material can be added to the aqueous formulation in approximately equal portions or unequal portions.

[0170] The aqueous preparation obtained in step c) preferably has a solid content corresponding to the solid content of the aqueous preparation provided in step a). It is therefore to be understood that the aqueous preparation obtained in step c) preferably has a solid content of up to 85.0% by weight, based on the total weight of the aqueous preparation obtained in step c). For example, the solid content of the aqueous preparation obtained in step c) is 0.5-82.0% by weight, preferably 0.5-80.0% by weight, most preferably 0.5-60.0% by weight, based on the total weight of the aqueous preparation obtained in step c).

[0171] In particular, the pH of the aqueous preparation obtained in step c) is preferably equal to or lower than 12, preferably 4-12, more preferably 6-11.5, most preferably 8.5-10.5.

[0172] Typically, the aqueous preparation obtained in step c) has a viscosity of preferably 50-2000 mPa·s, preferably 80-800 mPa·s, measured using a Brookfield DV-II viscometer equipped with a LV-3 spindle at a rotation speed of 100 rpm.

[0173] As mentioned above, the zinc oxide functionalized calcium carbonate composite material of the present invention can also be used to improve the storage stability of products as solid products. Therefore, the product can be any kind of solid product that needs to be stored and stabilized.

[0174] In one embodiment, the solid article can be a coating, a paint film, a varnish or coating, a paper coating, paper, paperboard, an adhesive, a sealant, a pigment, a fiber, a plaster, a plaster spray, a gypsum plasterboard, a binder, a thickener, gypsum and / or concrete.

[0175] In one embodiment, the total amount of the zinc oxide functionalized calcium carbonate composite material contained in the solid article is at least 10 ppm, such as 10-27000 ppm, preferably at least 25 ppm, such as 25-25000 ppm, more preferably at least 50 ppm, such as 50-20000 ppm, still more preferably at least 60 ppm, such as 60-15000 ppm, even more preferably at least 75 ppm, such as 75-10000 ppm, most preferably 75-5000 ppm, calculated relative to the total weight of the solid article.

[0176] It is understood that the solid product is preferably obtained by drying, setting or hardening an aqueous formulation as described above, i.e. a papermaking formulation, a paper coating formulation, a fiber formulation, a plastic formulation, an adhesive formulation, a metalworking fluid, a cooling fluid, a primer, a leveling compound, a pigment formulation, a titanium dioxide slurry, a concrete additive formulation, a binder formulation, a thickener formulation, a plaster, a coating, a render, a varnish and / or a paint formulation.

[0177] Therefore, the solid article preferably comprises at least one inorganic particulate material.

[0178] For example, the at least one inorganic particulate material is selected from natural ground calcium carbonate, natural and / or synthetic precipitated calcium carbonate, dolomite, calcium sulfate, kaolin, clay, barite, talc, quartz, mica, gypsum, aluminum hydroxide, aluminum silicate, titanium dioxide, magnesite, hydromagnesite, hydroxyapatite, perlite, sepiolite, brucite and mixtures thereof.

[0179] In one embodiment of the present invention, the at least one inorganic particulate material comprises natural ground calcium carbonate and / or synthetic precipitated calcium carbonate. Preferably, the at least one inorganic particulate material comprises natural ground calcium carbonate or synthetic precipitated calcium carbonate.

[0180] The natural ground calcium carbonate and / or the synthetic precipitated calcium carbonate may additionally be surface treated or may contain dispersants known to those skilled in the art.

[0181] If the solid preparation comprises at least one inorganic particulate material, the at least one inorganic particulate material may have a particle size distribution conventionally employed for materials involved in the type of product to be produced. Typically, 90% of the particles will have an esd (equivalent spherical diameter, measured by the well-known sedimentation method using a Micromeritics Sedigraph 5100 series) of less than 5 μm. Coarse inorganic particulate materials may have particles with an equivalent spherical diameter that is typically (i.e. at least 90% by weight) in the range of 1-5 μm. Fine inorganic particulate materials may have particles with an equivalent spherical diameter that is typically less than 2 μm, for example 50.0-99.0% by weight are less than 2 μm, preferably 60.0-90.0% by weight are less than 2 μm. Preferably, the at least one inorganic particulate material in the aqueous preparation has a weight median particle size d 50 The value is 0.1-5 μm, preferably 0.2-2 μm, most preferably 0.35-1 μm, for example 0.7 μm, measured using a Sedigraph™ 5100 from Micromeritics Instrument Corporation.

[0182] The solid preparation may further comprise a dispersant. Suitable dispersants according to the invention are preferably homopolymers or copolymers made from monomers and / or comonomers selected from the group consisting of acrylic acid, methacrylic acid, itaconic acid, crotonic acid, fumaric acid, maleic anhydride, isocrotonic acid, aconitic acid (cis or trans), mesaconic acid, sinapic acid, undecylenic acid, angelic acid, canneric acid, hydroxyacrylic acid, acrolein, acrylamide, acrylonitrile, dimethylaminoethyl methacrylate, vinylpyrrolidone, styrene, esters of acrylic acid and methacrylic acid and mixtures thereof, wherein salts of poly(acrylic acid) and / or poly(methacrylic acid) are preferably used as dispersants.

[0183] Preferably, if the aqueous formulation from which the solid preparation is prepared comprises a dispersant, the solid preparation comprises a dispersant.

[0184] Additionally or alternatively, the solid product comprises at least one organic particulate material. For example, the at least one organic particulate material is selected from carbohydrates such as starch, sugar, cellulose, modified cellulose and cellulose-based pulp, glycerol, hydrocarbons, water-soluble polymers such as polyacrylates, and mixtures thereof.

[0185] It should be noted that the solid product may include a buffer component selected from an amine-based buffer component, a monoalcohol-based buffer component, a primary alkanolamine-based buffer component, a hydroxide-based buffer component, and a mixture thereof. For example, the solid product may include a buffer component selected from the following items: ammonia, methylamine, dimethylamine, trimethylamine, diethylamine, propylamine, butylamine, hexylamine, amino-2-methylpropanol (AMP), monoethanolamine (MEA), monoisopropanolamine (MIPA), triethylenetetramine (TETA), calcium hydroxide, and a mixture thereof. Typically, the buffer component is included before the zinc oxide functionalized calcium carbonate composite material of the present invention is added.

[0186] The solid article according to the invention can be produced by methods known in the art, for example by drying, setting or hardening an aqueous preparation as described above, preferably a papermaking formulation, a paper coating formulation, a fiber formulation, a plastic formulation, an adhesive formulation, a metalworking fluid, a cooling fluid, a primer, a leveling compound, a pigment formulation, a titanium dioxide slurry, a concrete additive formulation, a binder formulation, a thickener formulation, a plaster, a coating, a render, a varnish and / or a paint formulation.

[0187] The present invention also relates to a method for improving the storage stability of a solid product, the method comprising the following steps:

[0188] a) providing a solid article comprising the zinc oxide functionalized calcium carbonate composite material as defined herein, the solid article preferably being a coating, a paint film, a varnish or a coating, a paper coating, paper, paperboard, an adhesive, a sealant, a pigment, a fiber, a plaster, a plaster spray, a gypsum plasterboard, a binder, a thickener, gypsum and / or concrete, and

[0189] b) moistening the surface of the solid product of step a) to obtain a stabilized solid product.

[0190] Regarding the definition of the zinc oxide functionalized calcium carbonate composite material and its preferred embodiments, reference may be made to the description provided above when discussing the technical details of the zinc oxide functionalized calcium carbonate composite material of the present invention.

[0191] According to step b) of the method of the present invention, the surface of the solid product of step a) is wetted to obtain a stabilized solid product. That is, the wetting of the surface of the solid product leads to the reactivation of the stabilizing ability of the zinc oxide functionalized calcium carbonate composite material of the present invention. In addition, it should be pointed out that the solid product does not provide stabilizing ability when it is not wetted.

[0192] It is therefore understood that when the zinc oxide functionalized calcium carbonate composite is present, the zinc oxide functionalized calcium carbonate composite is preferably capable of maintaining the pH of the wetted solid article at or below 12, preferably 4-12, more preferably 6-11.5 and most preferably 8.5-10.5. This prevents a decrease in the stability of the surface of the solid article.

[0193] Generally, the surface of the solid article of step a) can be wetted by any conventional method known to those skilled in the art.

[0194] It should be understood that step b) is preferably carried out by contacting the surface of the solid article of step a) with water, which is achieved, for example, by wetting, spraying, condensing, painting, dipping, immersing, etc., or if the surface of the solid article of step a) is exposed to moisture or rain.

[0195] The amount of the zinc oxide functionalized calcium carbonate composite material added to the solid product can be adjusted individually according to the solid product. The optimal amount to be employed within the defined range can be determined by preliminary tests and test series on a laboratory scale and by supplementary operational tests.

[0196] It is to be understood that step b) may be repeated one or more times.

[0197] The pH value of the solid product obtained in step b) is equal to or lower than 12, preferably 4-12, more preferably 6-11.5, and most preferably 8.5-10.5.

[0198] In view of the good results obtained, another aspect of the present invention relates to the use of a zinc oxide functionalized calcium carbonate composite material as defined herein in an aqueous formulation, preferably a papermaking formulation, a paper coating formulation, a fiber formulation, a plastic formulation, an adhesive formulation, a metalworking fluid, a cooling fluid, a primer, a leveling compound, a pigment formulation, a titanium dioxide slurry, a concrete additive formulation, a binder formulation, a thickener formulation, a plaster, a render, a coating, a varnish and / or a paint formulation, or a solid article, preferably a coating, a paint film, a varnish or a coating, a paper coating, paper, paperboard, an adhesive, a sealant, a pigment, a fiber, a plaster, a plaster spray, a gypsum plasterboard, a binder, a thickener and / or concrete.

[0199] Regarding the definitions of the product and the zinc oxide-functionalized calcium carbonate composite material and their preferred embodiments, reference may be made to the explanations provided above when discussing the technical details of the product and the zinc oxide-functionalized calcium carbonate composite material of the present invention.

[0200] It should be understood that the zinc oxide-functionalized calcium carbonate composite material improves the storage stability of the aqueous formulation or the solid product. BRIEF DESCRIPTION OF THE DRAWINGS

[0201] Figure 1 SEM involving zinc oxide functionalized calcium carbonate composites;

[0202] Figure 2 Concerning the SEM of a sample which is a blend of calcium carbonate with 10 wt% commercial zinc oxide. DETAILED DESCRIPTION

[0203] The scope and benefits of the present invention will be better understood based on the following examples, which are intended to illustrate certain embodiments of the invention and are non-limiting.

[0204] Example

[0205] The following measurement methods were used to evaluate the parameters given in the examples and claims.

[0206] Scanning electron microscopy (SEM)

[0207] The prepared samples were examined by the following equipment: Sigma VP field emission scanning electron microscope (Carl Zeiss AG, Germany) and a variable pressure secondary electron detector (VPSE) and / or a secondary electron detector (SE) with a chamber pressure of about 50Pa.

[0208] Particle size distribution

[0209] Unless otherwise specified, particle size as used herein is referred to as “d 50 ” and “d 98 The value is determined by the particle size determined by the sedimentation method, which is the analysis of the sedimentation behavior in the gravitational field. The Sedigraph of Micromeritics Instrument Corporation, USA, is used. TM The measurement was performed with a 5120. The method and the instrument are known to those skilled in the art and are commonly used to determine the particle size distribution of fillers and pigments. The measurement was performed in a 0.1 wt. % aqueous solution of Na4P2O7. A high-speed stirrer and ultrasound were used to disperse the sample.

[0210] Methods and instruments are known to those skilled in the art and are commonly used to determine the particle size of fillers and pigments.

[0211] BET surface area of ​​the material

[0212] The “specific surface area” (in m2) of a material as used throughout this document is 2The total surface area (m2 / g) of the material is determined by the Brunauer Emmett Teller (BET) method with nitrogen as the adsorption gas and by using an ASAP 2460 instrument from Micromeritics. This method is well known to those skilled in the art and is defined in ISO 9277:2010. Prior to the measurement, the sample is conditioned at 100°C under vacuum for a period of 60 minutes. 2 ) can be measured by the specific surface area of ​​the material (m 2 / g) and mass (g) to obtain the product.

[0213] Chemicals used to prepare ZnO-functionalized CaCO3 composites:

[0214] Zinc sulphate heptahydrate (Z4750), zinc nitrate hexahydrate (228737), zinc chloride (211273) and zinc acetate (383317) from Sigma-Aldrich, and distilled water. The calcium carbonate grade (GCC) used was OmyaCarb 1AV from Omya international.

[0215] Material preparation:

[0216] The first phase of this work was to evaluate the effects of the zinc salts used and the heat treatment steps. For this evaluation, the experimental protocol used was described below:

[0217] In a bottom flask, 750 mL of distilled water was heated to 80°C. 250 g of ground calcium carbonate was dispersed and the slurry was kept under stirring for 30 minutes. The zinc salt solution was dissolved in the water. The mixture was kept under stirring for 90 minutes. The amount and volume of the zinc salt solution are given in Table 1.

[0218] Table 1

[0219]

[0220] Subsequently, the slurry was filtered under pressure, the powder was washed with distilled water (three times the volume of the slurry water), and dried overnight at 150°C. 10 g of the material was heat treated in a muffle furnace at different temperatures (such as 300°C and 450°C) for 3 hours under static air. See Table 2 for details.

[0221] Table 2

[0222]

[0223]

[0224] The first analysis showed that the zinc material produced using zinc chloride salts provided better antimicrobial properties, especially when the material was heat treated in the range of 250-550°C.

[0225] In the following preparations, all samples were prepared using the same protocol. Zinc chloride was used as the zinc source. Details are shown in Table 3.

[0226] Table 3

[0227]

[0228]

[0229] It should be noted that the difference between the theoretical and experimental (i.e., actual) loadings of zinc can be reduced when high slurry temperatures are used. This effect can be attributed to the increase in interactions between reagents at high temperatures. In addition, BET is inversely proportional to the heat treatment temperature; BET decreases when the heat treatment temperature increases. From the XRD data, we also noticed a correlation with the heat treatment temperature. Zinc oxide species only appeared at temperatures above 250°C; below this value, no species was seen. In contrast, at temperatures below 250°C, side species such as smithsonite or hydrozincite were obtained. This shows that heat treatment temperatures above 250°C are crucial for obtaining ZnO species.

[0230] It is also noted that the obtained material is significantly different from a simple blend of the same calcium carbonate and commercial zinc oxide species. Figure 1 Display sample 12. Figure 1 It can be seen that the surface of calcium carbonate is fully functionalized / treated with zinc species.

[0231] Figure 2 The sample shown is a blend of calcium carbonate with 10% by weight of commercial zinc oxide. In contrast to the zinc oxide functionalized calcium carbonate composite; the white color relates to zinc oxide and the gray color relates to calcium carbonate. In contrast, this difference cannot be seen in the treated material because the calcium carbonate is modified with zinc oxide on its surface.

[0232] The above is also confirmed by, for example, Anca Dumbrava et al. "Characterization and applications of a new composite material obtained by green synthesis, through deposition of zinc oxide onto calcium carbonate precipitated in green seaweeds extract" (CERAMICS INTERNATIONAL, ELSEVIER, AMSTERDAM, NL, vol. 44, no. 5, December 13, 2017, pp. 4931-4936). This document relates to a composite material obtained by depositing zinc oxide on calcium carbonate precipitated in a green algae extract, so that the composite material obtained is not the result of a heat treatment, but a physical mixture of the components used. Anca Dumbrava et al. Figure 2 It is confirmed that the composite material obtained from this physical mixture can be clearly distinguished from the composite material obtained by the heat treatment required by the present invention. In particular, it can be seen that the composite material obtained from this physical mixture contains rod-shaped zinc oxide particles deposited only on a part of the surface of the calcium carbonate (similar to the composite material of the present invention). Figure 2 ).

[0233] Materials used:

[0234] Tryptic Soy Broth (TSB) (e.g. Sigma-Aldrich 22092)

[0235] Tryptic soy agar (TSA) (e.g. ready-made from Biomérieux)

[0236] PBS buffer

[0237] Pseudomonas aeruginosa (DSM 1128)

[0238] Standard incubator and shaker

[0239] Preparation of overnight cultures

[0240] Prepare an overnight culture of bacteria in 8 mL TSB. Grow the overnight culture at 30°C ± 2°C for 18 h ± 2 h. The titer of the overnight culture must be > 1 x 10 9cfu / ml .

[0241] Sample preparation and testing procedures:

[0242] Measure the OD of overnight cultures. 600 , and adjusted to 0.0005 in 10ml sterile TSB in a sterile 15ml Falcon tube. 50000ppm of the test substance was added to the tube with bacteria (in triplicate). The tube was cultured with shaking (180rpm) at 30°C. After 24h, 48h, 5d and 7d, 100μl of the cultured sample was inoculated onto TSA and cultured at 30°C for 24h to check the effectiveness of the antibacterial properties of the substance (see Table X). On the 7th, 8th and 9th days, an equal amount of bacteria (T=0) was reintroduced into each sample to further challenge the system and evaluate the antibacterial properties. The experiment was stopped after 12 days and the pH value of each sample was measured. The results are shown in Table 4.

[0243] Table 4:

[0244]

[0245]

[0246] ++ = No bacterial growth was observed on all three samples; + = Two of the three samples were clean; - = 1 sample was still clean; -- = All three samples were contaminated

[0247] result:

[0248] The above experiments clearly show that the samples activated at 325°C have the best antimicrobial activity (see Table 4, samples 2, 5, 9, 10 and 12). And the samples activated at 100°C or 550°C show significantly less or no antimicrobial activity, indicating that an activation temperature of about 250°C is critical for this effect. If only GCC (OmyaCarb 1AV) is activated at 325°C, no antimicrobial effect is observed (see sample 16), which clearly proves that the combination of the presence of zinc and an activation temperature of 250-550°C is essential.

Claims

1. A method for producing a zinc oxide functionalized calcium carbonate composite material, the method comprising the following steps: a) providing a calcium carbonate-containing material; b) providing at least one water-soluble or water-dispersible zinc ion source; c) preparing an aqueous suspension comprising the calcium carbonate-comprising material of step a) and the at least one water-soluble or water-dispersible zinc ion source of step b) under mixing, and heating the aqueous suspension to a temperature of at least 60° C.; d) drying the aqueous suspension of step c) to obtain a dried mixture; and e) heat treating the dried mixture obtained in step d) at a temperature in the range of 250-550° C. to obtain the zinc oxide functionalized calcium carbonate composite material.

2. The method according to claim 1, characterized in that: The calcium carbonate-containing material is selected from the group consisting of natural ground calcium carbonate, synthetic precipitated calcium carbonate and mixtures thereof, preferably natural ground calcium carbonate.

3. The method according to claim 1 or 2, characterized in that: The at least one water-soluble or water-dispersible zinc ion source is at least one zinc salt, preferably a zinc salt selected from zinc chloride, zinc sulfate, zinc nitrate, zinc citrate, zinc maleate, zinc acetate, zinc lactate and mixtures thereof, preferably, the zinc salt is zinc chloride.

4. A method according to any one of the preceding claims, characterised in that The calcium carbonate-containing material of step a) is provided in the form of an aqueous suspension, and / or the at least one water-soluble or water-dispersible zinc ion source of step b) is provided in the form of an aqueous suspension or aqueous solution or a solid material.

5. A method according to any one of the preceding claims, characterised in that The aqueous suspension of step c) is prepared by mixing the at least one water-soluble or water-dispersible zinc ion source of step b), preferably mixing the at least one water-soluble or water-dispersible zinc ion source of step b) as a solid material into the aqueous suspension of the calcium carbonate-containing material of step a).

6. A method according to any preceding claim, characterised in that The at least one water-soluble or water-dispersible zinc ion source of step b) is present in an amount (measured as Zn ions) of 1-40 wt.-%, preferably 3-35 wt.-%, most preferably 5-30 wt.-%, based on the total weight of the calcium carbonate-containing material.

7. A method according to any one of the preceding claims, characterised in that The heating in step c) is carried out at a temperature of 60-100°C, preferably 60-90°C, most preferably 60-75°C.

8. A method according to any preceding claim, characterised in that The drying in step d) is carried out by mechanical dehydration, filtration and / or evaporation.

9. A method according to any preceding claim, characterised in that The dried mixture has a solids content of 80-99.9% by weight, preferably 85-99.8% by weight, most preferably 90-99.5% by weight, based on the total weight of the obtained mixture.

10. A method according to any preceding claim, characterised in that The heat treatment in step e) is carried out at a temperature of 250-500°C, most preferably 250-450°C.

11. A method according to any preceding claim, characterised in that The zinc oxide functionalized calcium carbonate composite material has a BET specific surface area of ​​1.0-70.0 m 2 / g, preferably 1.0-65.0m 2 / g, most preferably 1.0-60.0m 2 / g, measured using nitrogen and BET method according to ISO9277.

12. A method according to any preceding claim, characterised in that The method comprises a further step f): mixing the zinc oxide functionalized calcium carbonate composite material and a dispersant.

13. A zinc oxide functionalized calcium carbonate composite material obtainable by the method according to any one of claims 1 to 12.

14. An article comprising the zinc oxide functionalized calcium carbonate composite material according to claim 13, which article is an aqueous preparation, preferably a papermaking formulation, a paper coating formulation, a fiber formulation, a plastic formulation, an adhesive formulation, a metalworking fluid, a cooling fluid, a primer, a leveling compound, a pigment formulation, a titanium dioxide slurry, a concrete additive formulation, a binder formulation, a thickener formulation, a plaster, a coating, a render, a varnish and / or a paint formulation, or a solid article, preferably a coating, a paint film, a varnish or a coating, a paper coating, paper, paperboard, an adhesive, a sealant, a pigment, a fiber, a plaster, a plaster spray, a gypsum plasterboard, a binder, a thickener, gypsum and / or concrete.

15. The preparation according to claim 14, which is an aqueous formulation comprising a dispersant.

16. Use of the zinc oxide functionalized calcium carbonate composite material according to claim 13 in an aqueous formulation, preferably a papermaking formulation, a paper coating formulation, a fiber formulation, a plastic formulation, an adhesive formulation, a metalworking fluid, a cooling fluid, a primer, a leveling compound, a pigment formulation, a titanium dioxide slurry, a concrete additive formulation, a binder formulation, a thickener formulation, a plaster, a render, a coating, a varnish and / or a paint formulation, or a solid article, preferably a coating, a paint film, a varnish or a coating, a paper coating, paper, board, an adhesive, a sealant, a pigment, a fiber, a plaster, a plaster spray, a gypsum plasterboard, a binder, a thickener and / or concrete.

17. The use according to claim 16, wherein the zinc oxide functionalized calcium carbonate composite material improves the storage stability of an aqueous preparation or a solid product.

Citation Information

Patent Citations

  • Surface-reacted calcium carbonate with functional cations

    EP3275947A1

  • Water-soluble polymers and / or copolymers possessing increased biodegradability, and their applications

    US5278248A